1976
DOI: 10.1083/jcb.71.2.575
|View full text |Cite
|
Sign up to set email alerts
|

Loss of endocytic capacity in aging Paramecium. The importance of cytoplasmic organelles.

Abstract: Aged cells have significantly fewer food vacuoles and ingest fewer bacteria than young cells. Loss of food vacuoles was explained by a decreasing difference in the food vacuole formation and excretion rates; the formation rate declined more rapidly than the excretion rate, approaching equivalence at 160 fissions, when the proportion of cells with no food vacuoles, in the presence of excess food, abruptly increased. A model for cellular aging is presented in which control of organelle numbers and cyclical inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 33 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…The presence of nucleic acid in microtubule-containing organelles has been deduced from cytochemical and analytical studies on the mitotic spindle (1)(2)(3)(4) and basal bodies (5)(6)(7)(8). Isolation of a specific basal body RNA has been reported (8), and recent electron microscopic studies have revealed specific RNase-sensitive structures in these organelles (9).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nucleic acid in microtubule-containing organelles has been deduced from cytochemical and analytical studies on the mitotic spindle (1)(2)(3)(4) and basal bodies (5)(6)(7)(8). Isolation of a specific basal body RNA has been reported (8), and recent electron microscopic studies have revealed specific RNase-sensitive structures in these organelles (9).…”
Section: Introductionmentioning
confidence: 99%
“…We then measured body weight, body length (nose to tail), and tail length. To analyze the differences between the mean variables from the five dietary 100 -25 5 groups we used the one-way analysis of varic ance (ANOVA) (16). Differences between mean initial and final body weights of each group were determined by the t-test (5, p. 71).…”
mentioning
confidence: 99%
“…In addition, young clones (30 to 40 fissions old) were used in preliminary experiments and were negative for fly ash, heated fly ash, and benzo(a)pyrene mutagenesis with induced or uninduced S-9. Ultraviolet induced damage is known to increase with age for given ultraviolet doses [39]. Perhaps the differences in sensitivity could reflect: 1) Induction of reparable lesions which are more efficiently repaired in some cells; 2) a suboptimal period in the cell cycle for treatment (the G2 period The resistance of some clones to fly ash or treated fly ash was routinely observed "Those values not connected by the same line are significantly different from one another (P < 0.05) using pairwise cornparisons of treatment groups proportions (6,30,411.…”
Section: Discussionmentioning
confidence: 99%